Prophylactic ranitidine treatment in critically ill children – a population pharmacokinetic study. (8th April 2013) - Hawwa, Ahmed F.; Westwood, Paul M.; Collier, Paul S.; Millership, Jeffrey S.; Yakkundi, Shirish; Thurley, Gillian; Shields, Mike D.; Nunn, Anthony J.; Halliday, Henry L.; McElnay, James C.
<x xml:space="preserve">Abstract</x> Aims To characterize the population pharmacokinetics of ranitidine in critically ill children and to determine the influence of various clinical and demographic factors on its disposition. Methods Data were collected prospectively from 78 paediatric patients (n = 248 plasma samples) who received oral or intravenous ranitidine for prophylaxis against stress ulcers, gastrointestinal bleeding or the treatment of gastro‐oesophageal reflux. Plasma samples were analysed using high‐performance liquid chromatography, and the data were subjected to population pharmacokinetic analysis using nonlinear mixed‐effects modelling. Results A one‐compartment model best described the plasma concentration profile, with an exponential structure for interindividual errors and a proportional structure for intra‐individual error. After backward stepwise elimination, the final model showed a significant decrease in objective function value (−12.618; P < 0.001) compared with the weight‐corrected base model. Final parameter estimates for the population were 32.1 l h−1 for total clearance and 285 l for volume of distribution, both allometrically modelled for a 70 kg adult. Final estimates for absorption rate constant and bioavailability were 1.31 h−1 and 27.5%, respectively. No significant relationship was found between age and weight‐corrected ranitidine pharmacokinetic parameters in the final model, with the covariate for cardiac failure or surgery being shown to reduce clearance significantly by a factor of 0.46. Conclusions Currently, ranitidine dose recommendations are based on children's weights. However, our findings suggest that a dosing scheme that takes into consideration both weight and cardiac failure/surgery would be more appropriate in order to avoid administration of higher or more frequent doses than necessary.